Consumer’s Attitude and Buying Behaviour of Organic/Green Products with Reference to Erode District - Prakash, M.; Mohan, S. (Journal of Commerce and Trade, 2016)
Development has become a necessity for man's survival today and for every step put forward by man, nature has had to take three backwards. We have developed all kinds of technical know-how to make our lives simpler, swifter and better in all ways but there has been very little movement towards making our efforts "Greener" too. We have managed to put man on moon but not without first putting a hole on the ozone layer. But today the environment has been kicking back stronger and harder than ever, making it impossible for man to overlook it. Organic farming is a form of agriculture that relies on techniques such as crop rotation, green manure, compost, and biological pest control. The study has been conducted to assess the overall consumers attitude and buying behaviour of Organic/ Green Product.. It was analysed using the model and the overall hypothesis was framed to determine the overall perception of the respondents about the consumer's attitude.